Alcohol Intoxication and Cognition: Implications on Mechanisms and Therapeutic Strategies - Jacob, Asha; Wang, Ping (Frontiers in Neuroscience, 2020)
Binge alcohol drinking is highly prevalent in young adults and results in 30% deaths per year in young males. Binge alcohol drinking or acute alcohol intoxication is a risk factor for developing alcohol use disorder (AUD). Three FDA approved drugs are currently in use as therapy for AUD; however, all of them have contra-indications and limitations. Structural brain imaging studies in alcoholics have shown defects in the brain regions involved in memory, cognition and emotional processing. Positron emission tomography (PET) using radiotracers (e.g., 18FDG) and measuring brain glucose metabolism have demonstrated diagnostic and prognostic utility in evaluating patients with cognitive impairment. Using PET imaging, only a few exclusive human studies have addressed the relationship between alcohol intoxication and cognition. Those studies indicate that alcohol intoxication causes reduction in brain activity. Consistent with prior findings, a recent study by us showed that acute alcohol intoxication reduced brain activity in the cortical and subcortical regions including the temporal lobe consisting the hippocampus. Additionally, we have observed a strong correlation between reduction in metabolic activity and spatial cognition impairment in the hippocampus after binge alcohol exposure. We have also demonstrated the involvement of a stress response protein, cold inducible RNA binding protein (CIRP), as a potential mechanistic mediator in acute alcohol intoxication. In this review, we will first discuss in detail prior human PET imaging studies on alcohol intoxication as well as our recent study on acute alcohol intoxication, and review the existing literature on potential mechanisms of acute alcohol intoxication-induced cognitive impairment and therapeutic strategies to mitigate these impairments. Finally, we will highlight the importance of studying brain regions as part of a brain network in delineating the mechanism of acute alcohol intoxication-induced cognitive impairment to aid in the development of therapeutics for such indication.